Pelatihan Chatgpt dalam Meningkatkan Kompetensi Manajemen Inovasi Pembelajaran Digital Berbasis Artificial Intelligence (AI) - Kintan, Nabila; Alam, Yuli; Martini, Martini; Hendriansyah, Hendriansyah; Novianti, Nita (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
Advances in artificial intelligence (AI) technology present new opportunities in the world of education. One of the latest innovations is ChatGPT, an AI-based model that can act as an interactive learning assistant. This research aims to socialize the potential for using ChatGPT in the learning process at Bina Sriwijaya Vocational School, especially in supporting students and teachers to improve the quality of learning. The methods used in this activity include presentations, demonstrations of the use of ChatGPT in learning, as well as interactive discussion sessions with students and teachers. The main focus of socialization is to explain the functions, advantages and limitations of ChatGPT as a learning aid, especially for technology, language and vocational skills-based subjects. The results of the activity show that students and teachers are enthusiastic about the potential use of ChatGPT, especially to improve understanding of material, provide suggestions on student projects, and help answer questions related to learning. However, there are several challenges, such as varying digital literacy among students and the need for further training for teachers in integrating these technologies effectively. This socialization concluded that ChatGPT has great potential to be applied in the learning process in vocational schools, especially in supporting independent and interactive learning approaches. However, further implementation requires careful planning, intensive training, and ongoing evaluation to ensure its use is optimal and in accordance with vocational education needs.